Pengaruh Penyuluhan Interaktif terhadap Peningkatan Pengetahuan Hipertensi pada Lansia di Sentra Meohai Kendari - Nurhijrianti Akib; Hariati Lestari (Jurnal Ventilator, 2025)
Hypertension is one of the major health problems in the elderly and increases the risk of cardiovascular disease. The low level of knowledge among the elderly about risk factors and prevention of hypertension is one of the challenges in controlling this disease. This study aims to determine the effectiveness of health education in increasing the knowledge of the elderly about hypertension at the Meohai Center in Kendari City. The study design used a pre-experimental approach with pre-test and post-test without a control group, involving 22 elderly individuals. The education was conducted through interactive lectures and visual educational media. The results showed an increase in the average knowledge score from 8.04 to 9.09 after the intervention, with a paired t-test yielding a p-value of 0.007, indicating a significant difference. These findings indicate that counseling is effective in increasing the knowledge of the elderly about hypertension. The implications of this study emphasize the importance of continuous education programs to support hypertension prevention efforts in the elderly